Effect of prototype armrest on comfort and muscle activity among selected male university motorcyclists during prolonged riding process - Alias, Ayuni Nabilah (2015)
Introduction: Motorcycles had become one of the most popular modes of transportation, well accepted by Malaysians. The awareness for the need safety in motorcycles has increased, with more inventions being applied to ensure safety and comfort motorcyclist. However, motorcyclist struggles with discomfort of their arm during prolonged riding as most of motorcycles in market are not equipped with arm posture support. Riding motorcycles without armrest can cause adverse health and psychological effects among motorcyclist in a long term. Therefore, the primary aim of this study is to examine the effect of using prototype armrest in terms of discomfort rating and muscle activity on the selected male university motorcyclists during prolonged riding process. Method: This study was experimental study among male students and staffs in Universiti Putra Malaysia (UPM). A total of 102 motorcyclists had participated in this study with 51 motorcyclists of experimental group were asked to sit on a motorcycle with armrest and another 51 motorcyclists of control group sat on a motorcycle without armrest. The experiment took place in a quiet room in a laboratory with adequate lighting. Each respondent had to attend experimental sessions on two different days (with a minimum three day interval between them). Each session had lasted for 2-hour. During the 2-hour session, a riding simulator system was displayed and respondents were asked to control the handlebar of motorcycle as in real road. The video screen of the riding simulator presented a view of road scenery with computer generated video simulating daytime riding condition. At every 15-minute interval, respondents were required to evaluate their discomfort level for all body part on the Borg’s CR-10 questionnaire. The Borg’s Scale Rating ( > 5) is considered as the ‘break point’, as point where the respondents rated their discomfort as strong. Therefore, this point considered where the respondents started to feel the discomfort in their parts of body. Besides that, Electromyography signals were used to monitor recorded muscle activity for the right and left arm of the respondents with the surface of electrodes attached.